FLORA LICHEN WESTERN MOUNTAINS VRANJE PLACE - Bogdanović, Gordana (Journal of process management and new technologies, 2016)
Lichen is a symbiotic plant built by the cells of algae and fungi hyphae. Algae are usually presented - green (Chlorophyta) or blue green (Cyanophyta), a mushroom commonly found is ascomycetae and sometimes basidiomycetae. Mushrooms receive oxygen and carbohydrates from algae, and they in turn provide water, CO2 and mineral salts. Lichens are often found on trees and rocks in unpolluted environments and can be used as a bioindicator species. In during 1999-2000. was realized a survey of epiphytic lichen flora of the western mountains in environment of Vranje. Sampling was carried out at 4 locations: Borino brdo, Krstilovica, Markovo Kale and Pljačkovica. Based on the collected and determined samples can be concluded that the study implemented of the area of 25 species of lichens of which: 8 as crust, leafy 12 and 5 shrub. The research results indicate that the lichen flora of the western mountains environments Vranje of a rich and diverse as a result of favorable geographic position, geological and soil composition, climate and plant cover that provide opportunities for the development and survival of lichens.